The effect of an elective cesarean section on maternal request on peripartum anxiety and depression in women with childbirth fear: a systematic review - Renske M. Olieman; Femke Siemonsma; Margaux A. Bartens; Susan Garthus-Niegel; Fedde Scheele; Adriaan Honig (BMC, 2017)
Abstract Background Obstetricians are often reluctant to grant requests for an elective cesarean section (ECS) due to childbirth fear. To date, it is unknown if an ECS on request improves mental well-being in the mother in the peripartum period and if possible beneficial effects on anxiety and depression could outweigh the increased risk of complications associated with a surgical delivery. A systematic review was conducted to explore the effect of ECS on request on peripartum anxiety and depression. Methods We searched on PubMed, PsychoInfo and Embase. Studies were included with primary data on anxiety and/or depression postpartum in women with childbirth fear who had requested an ECS. After full-text evaluation of 65 papers and quality analysis of four papers, three papers were included. Of one paper additional and yet unpublished data were provided. Studies varied in outcome measures, hence no meta-analysis was performed. Results Women who requested an ECS had higher antepartum depression and anxiety levels but no different postpartum depression levels than women who delivered vaginally. One study of good quality examined the effect of vaginal delivery in women preferring ECS: These women had significantly higher symptom levels of post-traumatic stress disorder (PTSD) and depression than women with normal vaginal delivery. Conclusions The prospect of an ECS does not lower antepartum anxiety and/or depression levels in women requesting an ECS. If women resolutely persist in wishing an ECS despite adequate counselling and/or psychiatric treatment, the risk of developing depressive and PTSD symptoms in case of vaginal delivery should be taken into account, and an ECS may be considered as a valid alternative.